OP12 Segmental vs Total Colectomy for Crohn's Disease of the colon in the biologic era. Results from the SCOTCH international, multicentric study. (21st January 2022) - Pellino MD- PhD- FRCS- FEBS Coloproctology- FA, G; Rottoli, M; Mineccia, M; Frontali, A; Celentano, V; Colombo, F; Ardizzone, S; Martí, M; Espín-Basany, E; Ferrero, A; Panis, Y; Poggioli, G; et al.
Abstract: Background: Previous studies suggested a role for segmental colectomy (SC) and total colectomy (TC) for colonic Crohn's disease (cCD). TC might reduce recurrence rates, at the cost of impaired quality of life and higher stoma rates. We compared the long-term outcomes of SC and TC. Methods: This is an international, multicentric study on data from the prospective databases of six centres. All consecutive patients operated on between 2000 and 2019 for cCD with SC or TC were included. Exclusion criteria were colorectal cancer, previous bowel resections, and lack of follow-up data. Disease extension was based on involvement of 1 to 5 colonic segments. Resection of 1–3 segments was classified as SC, resection of 4–5 segments as TC. Primary aim was surgical recurrence after SC vs TC. Secondary aims were perioperative complications, stoma formation rate, and predictors of recurrence. Results: Data of 687 (56.2% women) patients were analysed. Mean age at diagnosis and at surgery were 30±15.8 and 40.4±15.4 years. Disease duration was 10.4 ± 8.6 years. 16.6% of patients were A1, whereas most (62.2%) were diagnosed between 17 and 40 years. Isolated cCD (L2) was present in 61.1%, ileocolic CD (L3) in 38.9%, and concomitant jejuno-ileal CD (L4) in 3.2%. Most had stricturing (B2) cCD (41.9%). Active perianal disease was found in 28.9% patients. SC was performed in 285 patients, TC in 402. The latter more frequently had isolated cCD, inflammatory (B1) disease, current (37.8 vs 16.5%, p<0.001) or previous (56 vs 32.6%, p<0.001) perianal CD, and longer disease duration (11.3 ± 8.9 vs 9.2 ± 7.9, p<0.001). Postoperative complications and mortality were similar, but TC patients more frequently required 90-day readmission (6% vs 2.1%, p=0.02). Temporary (31.6 vs 21.4%, p<0.001) and definitive (39.3vs8%, p<0.001) stomas were more likely after TC. The 15-year cumulative surgical recurrence was 36%, more likely in the TC group (44 vs 27%, Log-Rank p=0.006), and it was not affected by the number of colonic segments involved (23 vs 28%, 1–3 vs 4–5 segments p=0.2) (Fig 1). In patients with 1–3 segments involved, postoperative treatment with biologics, compared to any other regimen, reduced the risk of recurrence (25 vs 51%, p<0.001), while early age at diagnosis (p=0.02) and perianal CD (p=0.01) increased the risk. Omission of biological therapy (HR 5.4, 95%CI 5.1–5.8 p<0.001), and paediatric diagnosis (HR 2.1, 95%CI 2.3–3.1 p<0.001) were the strongest predictors of recurrence in this subgroup. Conclusion: In this study, SC was safe, required less frequently stoma and repeated surgery, compared with TC. These findings question previous data on the topic and might be supported by the efficacy of postoperative biologic therapy on cCD.